Legionella, water and biotechnology - Cortés-Sánchez , A. D. J. (Regulatory Mechanisms in Biosystems, 2019)
Legionella spp. are microorganisms that are generally found in the aquatic environment (rivers, streams, lakes, among others). The importance in public health is in the fact that this bacterium is capable of multiplying and propagating in artificial aquatic systems (piping systems, storage tanks, fountains, and cooling towers), giving rise to diseases in humans called legionellosis, transmitted by inhalation of contaminated water droplets or aerosols and whose complications can lead to the death of the patient. Legionellosis is of worldwide distribution, Legionella pneumophila being the most commonly involved species in outbreaks and reported cases. The people most at risk are the elderly, people with weakened immune systems, and people with a history of smoking. Around the world, regulatory agencies and health organizations have issued and established recommendations with the purpose of controlling and preventing the risk of contracting this disease, which include the sanitation of water supplies, maintenance through regular cleaning and disinfection of facilities and devices for reducing the presence of this pathogen. The main objective of this review is to present in a general manner, aspects related to the disease known as legionellosis, its casual agents, habitat, transmission form, and phenotypic and metabolic characteristics. Likewise, the methods of control and prevention of these pathogens are presented, including a potential biotechnological alternative that can contribute to actions in favour of the protection of public health through the use of compounds with surface activity called biosurfactants.